Determinants of Airport–Airline Vertical Arrangements: Analytical Results and Empirical Evidence. (1st July 2015) - Yang, Hangjun; Zhang, Anming; Fu, Xiaowen
Many airports are making various vertical arrangements with their airline customers. This paper investigates the effects of such industry practices by analysing airport revenue sharing in a bargaining game. Our results suggest that, generally, airport–airline vertical arrangements are more likely to be formed when airlines have greater market power or higher costs, airport charges are higher, or the airport cares more about social welfare. Preliminary empirical tests confirm that public airports are more likely to form vertical arrangements, but other analytical results do not appear to be directly supported. Relevant policy implications and avenues for future research are provided.